Blended Learning in Dance Education: A Qualitative Study of Its Implementation among SIJB Students - Regita Azzahra Komarudin Putri; Agus Budiman; Fitri Kurniati (Universitas Negeri Medan, 2026)
This study is driven by the need for innovation in dance education at Sekolah Indonesia Luar Negeri (Indonesian Schools Abroad), where limited access to expert instructors remains a challenge, alongside the growing importance of technology in supporting skill-based learning. The study aims to describe the implementation of a blended learning model supported by audio-visual media in dance instruction at Sekolah Indonesia Johor Bahru (SIJB) and to examine the resulting learning outcomes. The study adopts a descriptive qualitative approach involving teachers, students, and expert instructors as participants. Data were collected through two days of direct observation, follow-up interviews conducted online via WhatsApp, questionnaires, and documentation. The analysis followed stages of data reduction, data display, and verification using triangulation techniques. The findings show that the learning process unfolds through interconnected stages, including video-based material distribution, independent learning, face-to-face practice, expert evaluation, and continued practice leading to performance. Audio-visual media serves as an initial learning resource that helps students build foundational understanding, while face-to-face practice with teacher guidance strengthens technical mastery of movements. Students’ responses reflect a generally positive trend, particularly in relation to interaction and direct learning, although variations in ability emerge due to differences in prior learning experience. Learning outcomes appear across cognitive, psychomotor, and affective domains, all of which develop throughout the process. In conclusion, the findings indicate that integrating audio-visual media with face-to-face learning supports a structured and sustained dance learning process, particularly in contexts with limited resources.